2015
DOI: 10.1097/mib.0000000000000473
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Ulcerative Colitis Is Associated with a High Rate of Readmissions at 30 Days

Abstract: Surgery for UC is associated with a high rate of readmission. Further prospective studies are necessary to determine the means to reduce these readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…It is not clear whether in-hospital complications or clinician anxiety are more strongly linked to the long length of stay. Similarly, readmission rates remain high, a finding that has also been noted in other large cohorts [28]. The SWORD provides evidence of readmission but not reason for readmission.…”
Section: Discussionsupporting
confidence: 66%
“…It is not clear whether in-hospital complications or clinician anxiety are more strongly linked to the long length of stay. Similarly, readmission rates remain high, a finding that has also been noted in other large cohorts [28]. The SWORD provides evidence of readmission but not reason for readmission.…”
Section: Discussionsupporting
confidence: 66%
“…Hanzlik et al have suggested that protocolized peri-operative teaching, such as the "Ileostomy pathway" which has been shown to reduce readmission rates in patients with new ostomies should be adopted in these cases. 16,17,22,[24][25][26][27] Of the post-operative complications, renal complications and urinary tract infections (7.6% each), were found to be significant risk factors for readmission and the similar findings were observed by Kassin et al as well. 3 Kelly et al also found that UTI was a significant factor for readmission.…”
Section: Discussionsupporting
confidence: 75%
“…The latter condition is most common. The reported risk factors for CD of the pouch include smoking, 4 family history of CD, 5 , 6 and being Ashkenazi Jews. 7 …”
Section: Discussionmentioning
confidence: 99%